Parameterized and Exact Computation 8th International Symposium, IPEC 2013, Sophia Antipolis, France, September 4-6, 2013, Revised Selected Papers - Gutin, Gregory; Szeider, Stefan (Theoretical Computer Science and General Issues,, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Symposium on Parameterized and Exact Computation, IPEC 2013, in Sophia Antipolis, France, in September 2013. The 29 revised full papers presented were carefully reviewed and selected from 58 submissions. The topics addressed cover research in all aspects of parameterized/exact algorithms and complexity including but are not limited to new techniques for the design and analysis of parameterized and exact algorithms, fixed-parameter tractability results, parameterized complexity theory, relationship between parameterized complexity and traditional complexity classifications, applications of parameterized and exact computation, and implementation issues of parameterized and exact algorithms.